Development and assessment of rhodamine B-loaded nanostructured lipid carrier-based in situ gel for enhanced brain targeting - Taher, Salam Shanta; Al-Kinani, Khalid Kadhem (Pharmakeftiki, 2025)
The development of effective drug delivery systems for brain targeting remains a significant challenge due to the restrictive nature of the blood-brain barrier. The intranasal route has emerged as a promising alternative, enabling direct drug transport to brain tissue via the nasal cavity. The primary objective of the present study was to investigate the incorporation of rhodamine B (a model fluorescent marker) into in situ gel-based nanostructured lipid carriers (NLCs) for potential brain targeting via the trigeminal or olfactory pathways. The formulated NLCs were characterized for particle size and polydispersity index (PDI). In vivo biodistribution studies were conducted in rats, which were divided into a control group and a treatment group receiving a single intranasal administration of rhodamine B-loaded NLC in situ gel. The distribution of the nanocarriers within brain tissues was assessed using fluorescence microscopy. The optimized formulation exhibited a mean particle size of 109.3 ± 9.8 nm and a PDI of 0.35 ± 0.07. Biodistribution analysis revealed a time-dependent accumulation of rhodamine B within brain tissues, with peak fluorescence intensity observed at 2 h post-administration. These findings suggest that rhodamine B-loaded NLC in situ gel enhances brain-targeting efficiency and may serve as a viable strategy for intranasal delivery of therapeutics intended for the management of central nervous system disorders.